K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 1

\(\dfrac{2^8\cdot2^{18}}{8^5\cdot4^6}=\dfrac{2^8\cdot2^{18}}{\left(2^3\right)^5\cdot\left(2^2\right)^6}=\dfrac{2^8\cdot2^{18}}{2^{15}\cdot2^{12}}\\ =\dfrac{2^{26}}{2^{27}}=\dfrac{1}{2}=0,5\)

8 tháng 4 2017

\(\frac{5.4^{15}.9^8-4.3^{17}.8^9}{5.2^{11}.6^{18}-7.2^{28}.27^6}\)\(=\frac{5.\left(2^2\right)^{15}.\left(3^2\right)^8-\left(2^2\right).3^{17}.\left(2^3\right)^9}{5.2^{11}.\left(2.3\right)^{18}-7.2^{28}.\left(3^3\right)^6}\)\(=\frac{5.2^{30}.3^{16}-2^2.3^{17}.2^{27}}{5.2^{11}.2^{18}.3^{18}-7.2^{28}.3^{18}}\)

                                            \(=\frac{5.2^{30}.3^{16}-2^{29}.3^{17}}{5.2^{29}.3^{18}-7.2^{28}.3^{18}}=\frac{2^{28}.3^{16}.\left(5.2^2-2.3\right)}{2^{28}.3^{16}.\left(5.2.3^2-7.3^2\right)}\)

                                             \(=\frac{5.2^2-2.3}{5.2.3^2-7.3^2}=\frac{5.4-6}{5.2.9-7.9}=\frac{20-6}{90-63}\)

                                               \(=\frac{14}{27}\)

8 tháng 4 2017

\(\frac{5.4^{15}.9^8-4.3^{17}.8^9}{5.2^{11}.6^{18}-7.2^{28}.27^6}=\frac{5.\left(2^2\right)^{15}.\left(3^2\right)^8-2^2.3^{17}.\left(2^3\right)^9}{5.2^{11}.\left(2.3\right)^{18}-7.2^{28}.\left(3^3\right)^6}\)\(=\frac{5.2^{30}.3^{16}-2^2.3^{17}.2^{27}}{5.2^{11}.2^{18}.3^{18}-7.2^{28}.3^{18}}=\frac{5.2^{30}.3^{16}-2^{29}.3^{17}}{5.2^{29}.3^{18}-7.2^{28}.3^{18}}\)\(=\frac{2^{29}.3^{16}.\left(5+2-3\right)}{2^{28}.3^{18}.\left(5+2\right)}\)\(=\frac{2.4}{3^2.7}=\frac{8}{63}\)

13 tháng 11 2015

 x= -660/7;y=-80/7;z=-100/7

25 tháng 2 2016

qwertyuiopasdfghjklzxcvbnm

a: \(=1995^2-\left(1995^2-1\right)=1995^2-1995^2+1=1\)

b: \(=18^8-18^8+1=1\)

c: \(=\left(163+37\right)^2=200^2=40000\)

11 tháng 4 2023

\(=>M=\dfrac{2^{28}.3^{18}.5-2^{29}.3^{20}}{2^{28}.3^{19}.5-2^{29}.3^{18}.7}\)

\(=\dfrac{2^{28}.3^{18}\left(5-2.3^2\right)}{2^{28}.3^{18}\left(3.5-2.7\right)}\)

\(=5-2.3^2\)

\(=5-2.9\)

\(=5-18\)

\(=-13\)

\(#Nzgoca\)

23 tháng 6 2018

Giải:

\(9^8.2^8-\left(18^4-1\right)\left(18^4+1\right)\)

\(=\left(9.2\right)^8-\left[\left(18^4\right)^2-1^2\right]\)

\(=18^8-18^8-1^2\)

\(=-1^2=-1\)

Vậy ...